PARENTING STYLES AND THEIR INFLUENCE ONHIGHLY SENSITIVE CHILDREN - Shimron, Bar (E-Journal VFU, 2025)
Parenting Styles and Their Influence on Highly Sensitive Children Parenting styles significantly shape the emotional and behavioral development of children, particularly those identified as Highly Sensitive Children (HSCs), who constitute approximately 15 to 20 percent of the population (Parents,2024). These children are characterized by heightened sensitivity to sensory input and emotional cues, which makes their parenting needs distinct and crucial for their well-being. Understanding the nuances of various parenting styles—such as authoritative, authoritarian, permissive, and uninvolved—allows parents and caregivers to adapt their approaches to support the unique emotional landscapes of HSCs effectively. (Schoenfeld, A. 2021, Parenting for Brain) Research highlights that authoritative parenting, marked by a balance of high demands and responsiveness, tends to yield positive outcomes for HSCs, fostering resilience, self-advocacy, and emotional regulation. (Mak, Y. W., & Zhang, Z. 2018, Womack, L. 2023) In contrast, authoritarian and uninvolved parenting styles can exacerbate the challenges faced by sensitive children, potentially leading to increased anxiety, emotional distress, and difficulties in social interactions. (Parenting for Brain, Schoenfeld, A. 2021). As HSCs often interpret experiences through a lens of vulnerability, it is essential for parents to adopt strategies that validate their emotions and create nurturing environments conducive to growth and self-expression. (Allen, R. 2021, Moller, J. 2011) Controversies surrounding parenting styles often arise from societal pressures to conform to traditional disciplinary methods that may not align with the needs of highly sensitive children. Such approaches can trigger anxiety and emotional breakdowns, underscoring the necessity for a gentler, more empathetic parenting approach tailored to HSCs. (Allen, R. 2021, Little Otter, Kumar, R.2020) By prioritizing emotional validation and creating calm, structured environments, parents can significantly enhance the emotional and psychological well-being of their highly sensitive children, enabling them to thrive academically and socially. (Highly Sensitive Child. n.d., Neurodivergent Insights. (n.d.) Ultimately, recognizing the intricate interplay between parenting styles and the unique characteristics of HSCs is vital for fostering optimal development, mitigating potential challenges, and embracing the strengths these children possess. (Highly Sensitive Child. n.d., Neurodivergent Insights. (n.d.) Understanding these dynamics empowers parents to make informed choices that nurture their children’s individuality and emotional health.